2020
DOI: 10.3390/cancers12113245
|View full text |Cite
|
Sign up to set email alerts
|

Deep Phenotyping Reveals Distinct Immune Signatures Correlating with Prognostication, Treatment Responses, and MRD Status in Multiple Myeloma

Abstract: Despite recent advances, Multiple Myeloma (MM) remains an incurable disease with apparent heterogeneity that may explain patients’ variable clinical outcomes. While the phenotypic, (epi)genetic, and molecular characteristics of myeloma cells have been thoroughly examined, there is limited information regarding the role of the bone marrow (BM) microenvironment in the natural history of the disease. In the present study, we performed deep phenotyping of 32 distinct immune cell subsets in a cohort of 94 MM patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 54 publications
2
31
0
Order By: Relevance
“…Nonetheless, a small proportion of persistent MRD-positive patients did not progress at the data cutoff, suggesting that an MGUS-like indolent phenotype could still be present and thus changing treatment should be contraindicated. Moreover, a precise immune profiling by flow cytometry can offer complementary information to the simple quantification of MRD levels and may contribute to identifying a subset of patients that, albeit being MRD-positive, can still experience prolonged survival due to a unique immune signature (ex: with a more prominent regeneration of mature B lymphocytes) with probably a competent immune surveillance keeping myeloma burden in repression 13 , 14 . It would be informative to evaluate the genomic profile of these residual MM cells or to monitor the trend of MRD kinetics, as previously done for other hematologic diseases 15 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a small proportion of persistent MRD-positive patients did not progress at the data cutoff, suggesting that an MGUS-like indolent phenotype could still be present and thus changing treatment should be contraindicated. Moreover, a precise immune profiling by flow cytometry can offer complementary information to the simple quantification of MRD levels and may contribute to identifying a subset of patients that, albeit being MRD-positive, can still experience prolonged survival due to a unique immune signature (ex: with a more prominent regeneration of mature B lymphocytes) with probably a competent immune surveillance keeping myeloma burden in repression 13 , 14 . It would be informative to evaluate the genomic profile of these residual MM cells or to monitor the trend of MRD kinetics, as previously done for other hematologic diseases 15 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the elucidation of the exact molecular interactions within the BM and the identification of unique immune signatures that may have clinical utility in terms of prognostication and/or drug efficacy prediction is a very active field in MM research [40]. In this context, we recently reported on unique BM signatures that are predictive of different responses to the same VRD induction therapy [18]. Moreover, we showed that, despite the apparent innate heterogeneity in the BM subset distribution post ASCT, patients with the same MRD status (positive vs. negative) shared commonmicroenvironmental features that allowed for their efficient clustering in the two groups [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we recently reported on unique BM signatures that are predictive of different responses to the same VRD induction therapy [18]. Moreover, we showed that, despite the apparent innate heterogeneity in the BM subset distribution post ASCT, patients with the same MRD status (positive vs. negative) shared commonmicroenvironmental features that allowed for their efficient clustering in the two groups [18]. In order to assess whether the presence of APCs in grafts could result in a different BM profile, we evaluated the niche composition on day 100 post ASCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some of these patients, laboratory or imaging techniques can identify some (minimal) residual disease (Figure 1C). Understanding of the molecular features of this minimal residual disease (MRD) and identification of new targets expressed by these MRD cells would allow us to eradicate these residual cells and offer a another option for curing this malignancy [10]. Finally, new treatment strategies are required for patients presenting a refractory disease (Figure 1D).…”
mentioning
confidence: 99%